Ranking Iranian Accredited Laboratories with Proficiency Tests Using Promethee Method - Amini, Mousa; Alinezhad, Alireza; Najafabadiha, Hamid (Review of Industrial Engineering Letters, 2014)
The rapid pace of changing technology is leading to high rate of import and export between different countries. In outsourcing governmental organizations duties to private sectors, it is a need to control sectors and they should be under assessment policy. This research has been developed to show how the accredited laboratories of Iranian standard (ISIRI) can be assessed for their technical servicing using the Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE) in combination with proficiency testing inter- laboratories comparison, in order to rank them for an urgent or crucial need of testing any kind of goods or products under compulsory regulation or national standard for their quality or safety aspect. The proposed approach, therefore, allows a decision to be made with confidence that the alternative (laboratory) chosen has best performance for conformity assessment.